Prężność i jakość życia uczniów jako predyktory rozwoju. Przypadek uczniów ze środowiska małomiasteczkowego - Gniedziejko, Agnieszka (Pedagogika Społeczna Nova, 2026)
A high level of resilience plays a very important role in the functioning of young people. It protects people from undertaking various risky and harmful behaviors. It also has a positive effect on adaptation to changing conditions. A resilient person is able to cope with various, difficult situations, crises or tasks posed by the environment, which are present in the life of every person. The aim of the conducted research was to find out whether mental resilience is associated with the perceived quality of life of people aged 15–18. 212 students of the General Secondary School in Dąbrowa Białostocka were examined using the scales: “Scale of measurement of resilience – SPP-18” by N. Ogińska-Bulik and KIDSCREEN-27. It turned out that there is a relationship between mental resilience and quality of life. Both variables are at an average level. The results of the research may be useful in creating and implementing lesson plans that will be aimed at supporting the development of specific groups of students. Moreover, the knowledge of education staff should be updated in this area.